Antineoplastic agents aggravate the damages caused by nicotine on the peri-implant bone: an in vivo histomorphometric and immunohistochemical study in rats - de Almeida, Juliano Milanezi [UNESP]; Ervolino, Edilson [UNESP]; Gusman, David Jonathan Rodrigues [UNESP]; Fiorin, Luiz Guilherme [UNESP]; Alves, Breno Edson Sendão [UNESP]; Guastaldi, Fernando Pozzi Semeghini; Matheus, Henrique Rinaldi [UNESP] (Springer Nature, 2022)
Objective: To assess the interaction between chemotherapy and normal tissues is critical to assure quality of life during and after the treatment of cancer. This study evaluated the influence of cisplatin (CIS) and 5-fluorouracil (5-FU) over the peri-implant tissues around osseointegrated titanium implants in animals previously exposed to nicotine. Materials and methods One hundred twenty male rats were divided into two groups, receiving via subcutaneous injection, either physiological saline solution (PSS) (n = 30) or nicotine hemissulfate (NIC) (n = 90) for 30 days prior to implants’ placement. One titanium implant (4.0 × 2.2 mm) was installed in each tibia of all animals. PSS and NIC were continued for 30 days after surgery. Five days after cessation, rats were subdivided into three subgroups in accordance with systemic treatments with either PSS, CIS, or 5-FU. Euthanasia was performed at 50, 65, and 95 days post-surgery. Histometric, histopathological, and immunohistochemical analyses were performed. Results: NIC-CIS and NIC-5FU presented lower BIC (50, 65, and 95 days) and bone area fraction occupancy (BAFO) (65 and 95 days) than group NIC. Intense inflammatory infiltration, severe tissue breakdown, reduced expression of bone formation biomarkers, and upregulation of TRAP were observed in NIC-CIS and NIC-5FU when compared with group NIC. TRAP expression was significantly higher in NIC-5FU as compared with NIC-CIS at 50 and 95 days. Groups NIC, NIC-CIS, and NIC-5FU presented statistically significant negative impact in all outcome parameters than group PSS. Conclusion: CIS and 5-FU severely disrupted the peri-implant tissues around osseointegrated implants in animals previously exposed to nicotine. Clinical relevance: Assessing the interaction between chemotherapy and normal tissues is critical to assure quality of life during and after the cancer treatment.
Keywords: Antineoplastic agents; Cisplatin; Dental implants; Fluorouracil; Nicotine; Osseointegration